2012
DOI: 10.1080/08841241.2012.736884
|View full text |Cite
|
Sign up to set email alerts
|

Students as global citizens: strategies for mobilizing studies abroad

Abstract: Students as global citizens: strategies for mobilising studies abroadUniversities globally are increasingly seeking to improve the international mobility of their students. There are several latent benefits that accrue to a university whose students and staff actively participate in international exchange programs. Essentially this can lead to an increase in the university's international reputation, opportunities for benchmarking against best practices, capacity to develop international relationships, diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
(34 reference statements)
1
11
0
Order By: Relevance
“…In line with Sison and Brennan (2012), Williams and Omar (2013), and Duesterhaus & Duesterhaus (2014), the results of the present study confirm that higher education institutions invest in marketing activities online. When it comes to social media, European and North American universities and colleges opened accounts in social media networks (in average: EU-1.91; US-1.88), content sharing platforms (in average: EU-1.81; US-2.38), and microblogs (in average: EU-1.00; US-1.18).…”
Section: Discussionsupporting
confidence: 90%
“…In line with Sison and Brennan (2012), Williams and Omar (2013), and Duesterhaus & Duesterhaus (2014), the results of the present study confirm that higher education institutions invest in marketing activities online. When it comes to social media, European and North American universities and colleges opened accounts in social media networks (in average: EU-1.91; US-1.88), content sharing platforms (in average: EU-1.81; US-2.38), and microblogs (in average: EU-1.00; US-1.18).…”
Section: Discussionsupporting
confidence: 90%
“…Business organizations are also placing increased value on college students' study abroad experiences (Trooboff et al, 2008). SAPs may provide benefits to countries as well, such as greater opportunities to enter global markets or to develop better international relationships (Sison & Brennan, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent survey of study abroad alumni indicates that they found entry-level positions sooner and more often in their chosen fields, while also earning higher starting salaries (Cook-Anderson, 2013). In addition to students, SAPs also benefit countries (Sison & Brennan, 2012) by providing greater opportunities for international trade, greater capacity to develop international relationships and greater levels of understanding of cultural differences.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations